Proteomic analysis of a copper mine isolated fungus Rhizopus microspores IOC 4686 when exposed to copper sulfate - Meriellen Dias; José Thalles Jocelino Gomes de Lacerda; Lidiane Maria Andrade; Claudio Augusto Oller do Nascimento; Enrique Eduardo Rozas; Maria Anita Mendes (Archive of Biochemistry - Peertechz Publications, 2022)
The fungus Rhizopus microsporus, known for its absorption capacity for toxic metals was used to understand the green metal recovery via analysis of its physiology under metal stress conditions through proteomic methods. To investigate the effects of copper stress on fungus, R. microsporus IOC 4686, isolated from the mine environment, was exposed to copper ions (50mgL-1) for 48 h. This study was performed only on copper exposure. Tryptic and chymotryptic extracts of proteins were analyzed by nano- liquid chromatography-tandem mass spectrometry, identification was performed by PEAKS Studio 8.5. Proteins were classified according to their molecular function and biological process. Enzymes, such as catalase, superoxide dismutase, and cytochrome c peroxidase were found in the presence and absence of copper ions. However, only in presence of copper ions, was observed the presence of heat shock proteins (HPS 20, HPS 70, and HPS 78) and metalloproteins (GrpE protein homolog and cytochrome P450). These classes of proteins have been produced by cells in response to stress conditions. The control group (absence of copper ions) also presented antioxidant enzymes suggesting that the fungus isolated from the mine environment already has adapted to the copper. The presence of these proteins suggested a physiological response of R. microsporus IOC 4686 to oxidative stress induced by copper.